Utilização de resíduos industriais como corretivo de acidez do solo e fonte de nutrientes para o cafeeiro - Nogueira, Natiélia Oliveira (2014)
The use of industrial residues in agriculture has shown potential when used as soil acidity correction or fertilizers. Moreover, it presents benefits to the environment by reducing environmental impacts due to the large amount of residues generated in the